VISUAL IDENTITY GUDANG CREATIVE DESIGN DALAM MENINGKATKAN BRAND AWARENESS - Abdul Hamdanil; Syafwandi Syafwandi (Universitas Negeri Padang, 2021)
Gudang Creative Design is a service business engaged in graphic design and photography that is currently developing in Sungai Pua District, Agam Regency. Gudang Creative Design was formed in 2017 and is managed by Yoli Ade Saputra as the owner and founder of Gudang Creative Desain until now. This business is still relatively new and requires a visual identity that includes logos, colors, and fonts, as well as rules in their application, in accordance with the guidelines set by the designer in the manual books as the main medium, in order to form a consistent identity, improve the business image, as well as differentiate it with other competitors. The purpose of this research is to design visual identity and other promotional media. The theories used in this research are brand theory, promotion theory, awareness theory and logo theory.The design method that I use is the 4D method which is used to support the creation of the design concept of visual identity.The expected results are in the form of main media, namely manual books, then supporting media such as business cards, stamp id cards, letterheads, envelopes, posters, x-banner, stamps, customer desks, car branding and articles to be published in the DKV journal FBS UNP Padang.Keyword : Branding , Promosi, Awareness dan Logo